Exploring multiple efficacies through sensory relatedness at Restore, an Oxfordshire mental health charity - Peng, Y (2023)
This thesis responds to the demand for an anthropological evaluation of the service at Restore. It is an exploration of the multiple efficacies in this community mental health charity. Empirically, I work with archival materials about the hospital and community spaces where Restore was incubated and founded. I also present ethnographic accounts of the gardening, craftwork, and catering work at Restore’s three recovery groups in Oxford and Banbury. I use a diversity of research methods to study these empirical materials, including participant learning and experience, visual archives analysis, spoken discourse analysis, photo-elicitation and semi-structured interviews.